Microvascular Decompression for Trigeminal Neuralgia: A Prospective, Multicenter Study. Issue 4 (29th July 2021) - Mizobuchi, Yoshifumi; Nagahiro, Shinji; Kondo, Akinori; Arita, Kazunori; Date, Isao; Fujii, Yukihiko; Fujimaki, Takamitsu; Hanaya, Ryosuke; Hasegawa, Mitsuhiro; Hatayama, Toru; Inoue, Tooru; Kasuya, Hidetoshi; et al.
Abstract: BACKGROUND: Microvascular decompression (MVD) is the most effective procedure for the long-term management of trigeminal neuralgia (TGN). However, retrospective and single-center studies are inherently biased, and there are currently no prospective, multicenter studies. OBJECTIVE: To evaluate the short- and long-term outcomes and complications in patients with TGN who underwent MVD at specialized Japanese institutions. METHODS: We enrolled patients with TGN who underwent MVD between April 2012 and March 2015. We recorded their facial pain grade and complications at 7 d (short term), 1 yr (mid-term), and 3 yr (long term) postoperatively. RESULTS: There were 166 patients, comprising 60 men and 106 women (mean age 62.7 yr). Furthermore, 105 patients were aged over 60 yr. We conducted neuromonitoring in 84.3% of the cases. The complete pain relief, mortality, and complication rates at the short-term follow-up were 78.9%, 0%, and 16.3%, respectively. Overall, 155 patients (93.4%) completed the long-term follow-up, with the complete pain relief and complication rates of 80.0% and 5.2%, respectively. CONCLUSION: In the hands of experienced neurosurgeons, MVD for TGN can achieve high long-term curative effects. In addition, complications are uncommon and usually transient. Our results indicate that MVD is an effective and safe treatment for patients with TGN, including elderly patients. Graphical Abstract: